Immunization efficacy of cryopreserved genetically attenuated Plasmodium berghei sporozoites - Prinz, Henriette; Sattler, Julia M.; Ripp, Johanna; Frischknecht, Friedrich (Parasitology research, 2018)
Malaria is transmitted through the injection of Plasmodium sporozoites into the skin by Anopheles mosquitoes. The parasites first replicate within the liver before infecting red blood cells, which leads to the symptoms of the disease. Experimental immunization with attenuated sporozoites that arrest their development in the liver has been extensively investigated in rodent models and humans. Recent technological advances have included the capacity to cryopreserve sporozoites for injection, which has enabled a series of controlled studies on human infection with sporozoites. Here, we used a cryopreservation protocol to test the efficiency of genetically attenuated cryopreserved sporozoites for immunization of mice in comparison with freshly isolated controls. This showed that cryopreserved sporozoites are highly viable as judged by their capacity to migrate in vitro but show only 20% efficiency in liver infection, which impacts their capacity to generate protection of animals in immunization experiments.
Gesehen am 15.05.2020